Handbook of long-term care administration and policy - Mara, Cynthia Massie; Olson, Laura Katz (Public administration and public policy, 2008)
Covers topics such as public perception, understanding system failure, and the tensions between the social model and the medical model. This book focuses on recipients and their care givers, and emphasizes services, exploring models that confront the barriers to achieving coordination of care